As técnicas jornalísticas no G1 em 1 minuto: estratégias de visibilidade para o G1 - Freitas, Catarina Ferreira Sarmento de (2019)
With the technological development and the expansion of new media, journalism began to modernize its format. The technical and technological aspects overlap functionalism and content. However, it is questioned to what extent the journalistic discourses of media conglomerates are able to fulfill the social function of journalism. Thus, it is sought to understand how journalistic techniques are used as a marketing strategy for platform visibility. This dissertation proposes to understand convergent journalism as a multiplatform practice, anchored in new technologies. And thus, to perceive the symbolic dimension of journalistic production. For this, the G1 in 1 Minute is used as object of study, since this bulletin allows a communication and mediatic bridge between the two platforms: television and hypermedia. In this way, the journalistic organizational structures are studied, as well as the demands and characteristics of the research object, within the television space and its correlation with cyberspace.